Pendampingan Konseling Gratis Melalui Aplikasi SIAPPAK : Untuk Meningkatkan Kesejahteraan Mental Masyarakat - Fadhiilah, Rofi'atul; Wikartika, Ira (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Free counseling assistance through the SIAPPAK application is the latest innovation from the Surabaya government to improve the mental well-being of the community in the Bubutan sub-district. This research aims to explore the effectiveness of free counseling assistance through the SIAPPAK application in improving people's mental well-being. In the context of people's mental well-being, the SIAPPAK application can be an innovative solution for dealing with various psychological problems. This research makes an important contribution to the development of affordable mental health services, especially in settings that may have limited access to traditional services. The practical implications of these findings can provide a basis for the expansion and development of similar applications to maintain and improve the mental well-being of society. This research aims to 1. Improve the mental well-being of the community in Bubutan sub-district 2. provide access to affordable mental health services 3. Increase mental health awareness.